Breakdown in Hypomineralization in Deciduous Teeth: An Association between Anthropometric, Orthodontic and Dental Caries Data - Rafael Vrijdags Calado; Paulo Tavares Mendonça Neto; Lisa Danielly Curcino Araujo; Daniela Maria Carvalho Pugliesi; Patrícia Batista Lopes do Nascimento; Dayse Andrade Romão; Valdeci Elias dos Santos Júnior (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the association of dental tissue fracture related to hypomineralization and its association with anthropometric, orthodontic, and dental caries in deciduous teeth. Material and Methods: A cross-sectional study was conducted with 313 children aged 6 to 10. Data were collected through clinical examination based on criteria from the European Academy of Pediatric Dentistry (EAPD) for the diagnosis of hypomineralization. Facial biotype analysis was conducted based on collected data. Orthodontic data were collected in terms of Angle classification and malocclusions. The diagnosis of dental caries was guided by ICDAS II (International Caries Detection and Assessment System) parameters. Statistical analysis involved descriptive analysis, Fisher's exact test, and the chi-squared test. Results: 23.3% of children had hypomineralization in deciduous, and 20.4% had post-eruptive breakdown preceded by hypomineralization (PEBH). The analyses indicated that weight, height, facial biotype, and malocclusions are not significantly associated with PEBH. Dental caries was associated with the presence of hypomineralization (p<0.001) and breakdown in deciduous teeth (p<0.001). Conclusion: An association between dental caries, hypomineralization, and PEBH was found for deciduous teeth. Orthodontic and anthropometric parameters were not associated with post-eruptive breakdown preceded by hypomineralization.